Understanding Indonesian history, interest in learning history and national insight with nationalism attitude - Johan Setiawan; Aman Aman; Taat Wulandari (International Journal of Evaluation and Research in Education (IJERE), 2020)
The purpose of this study was to investigate the relationship of understanding Indonesian history, interest in learning history and national insight with the nationalism attitude among State Senior High School students in Ngaglik subdistrict, Yogyakarta. The data collection used tests and questionnaires distributed to 126 students who were the respondents, the data were analyzed quantitavely using SPSS version 21. The validity test of the instrument employed biserial point correlation and reliability test using the Kuder–Richardson Formula 20 (KR 20) formula. Analysis prerequisite tests include normality test, linearity test, and multicollinearity test. The hypotheses were tested using Pearson’s product moment correlation and multiple correlation The results of the data analysis shows: (a) there is a positive and significant relationship between understanding Indonesian history with nationalism attitude; (b) there is a positive and significant relationship between interest in learning history and nationalism attitude; (c) there is a positive and significant relationship between national insight and nationalism; and (d) there is a simultaneously positive and significant relationship between understanding of Indonesian history, interest in learning history, and national insight with nationalism attitude.